EVALUATING TIME OPERATION OF FLOATING CRANE ON COAL’S LOADING OF PT HANDIL BHAKTI PERSADA IN TABONEO HARBOUR SOUTH KALIMANTAN - Yuliantini Yuliantini; Bagus Aprian (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
PT Handil Bhakti Persada, a coal mining company catering its domestic and international customers, owns a terminal to support its sales operation. This study was focusing on the time operation of floating crane on coal’s loading in Taboneo Harbour, South Kalimantan in 2013. The objectives of this study were (1) to know the real time floating crane operation (2) to know time operation’s planning of floating crane (3) to know the efforts done by the company on real time operation of floating crane. This study used descriptive qualitative approach to find out the loading level of coal. Horizontal and vertical analyses are used in this study. The horizontal analysis was used to compare real time activities both absolute and relative on certain time achievement. Whilst vertical analysis was used to describe activities trends on certain time achievement. This study showed that the real time coal’s loading production on 2011, 2012, 2013 did not reach the target. This study recommended PT Handil Bhakti Persada to (1) make schedule for the operators (2) maintain loading equipment (3) supervise operational budget.